Pengembangan Bahan Ajar PAI pada Lembaga Pendidikan Tinggi Islam dalam Era Digital - Arman Paramansyah; Latipatinupus; Adr Sunanjar; Kiki Agustianto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research was conducted to find out what concepts are relevant to be developed in Islamic universities in this digital era. The research methodology used is a literature review by collecting relevant information which is then organized and arranged thematically to obtain a comprehensive understanding. The research results show that there are challenges for students such as content authenticity, privacy, and technology accessibility gaps. So the concept developed is digital literacy which provides an understanding of the importance of protecting personal data and awareness of the dangers of irresponsible misuse of data